2015
DOI: 10.1523/jneurosci.1813-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Brief Dark Exposure Reduces Tonic Inhibition in Visual Cortex

Abstract: Tonic inhibition mediated by extrasynaptic GABA A receptors (GABARs) sensing ambient levels of GABA can profoundly alter the membrane input resistance to affect cellular excitability. Therefore, regulation of tonic inhibition is an attractive mechanism to control the levels of cortical firing. In cortical pyramidal cells, tonic inhibition is regulated by age and several neurotransmitters and is affected by stroke and epilepsy. However, the possible role of sensory experience has not been examined. Here, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Recently, it has been shown that dark exposure reduces tonic inhibition in visual cortex (Huang et al ., ) and that monocular deprivation alters early components of visual evoked potentials as well as producing a GABA concentration decrement in the primary visual cortex of adult humans (Lunghi et al ., ,b). Interestingly, GABA is suggested to play a key role in generating and maintaining alpha oscillations (Klimesch et al ., ; Jensen & Mazaheri, ), and pharmacological GABA enhancers can reduce spontaneous alpha amplitude (Lozano‐Soldevilla et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that dark exposure reduces tonic inhibition in visual cortex (Huang et al ., ) and that monocular deprivation alters early components of visual evoked potentials as well as producing a GABA concentration decrement in the primary visual cortex of adult humans (Lunghi et al ., ,b). Interestingly, GABA is suggested to play a key role in generating and maintaining alpha oscillations (Klimesch et al ., ; Jensen & Mazaheri, ), and pharmacological GABA enhancers can reduce spontaneous alpha amplitude (Lozano‐Soldevilla et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The latency and integration time of visual processing – from retinal to higher processing sites – progressively increases at low‐luminance (Kammer et al ., ), as well as the alpha amplitude (Min et al ., ; Brodoehl et al ., ), and the frequency of behavioural visual oscillations (Benedetto et al ., ). Moreover, brief dark exposure produces adaptive changes in cortical excitability (Huang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…This view has been challenged by experiments with different models of visual deprivation, which leads to an early decrease in spiking activity in visual cortex followed by an increase. Several studies found that these changes in firing rates are fast and may precede synaptic changes, with one of the key underlying mechanisms being the disinhibition of excitatory pyramidal neurons in response to decreased activity of inhibitory interneurons (Aton et al., ; Huang, Hokenson, Bandyopadhyay, Russek, & Kirkwood, ; Kuhlman et al., ). Other recent experiments also found that changes in firing rate are not the ultimate consequence of synaptic plasticity, as is often assumed, but rather a necessary condition for the occurrence of synaptic homeostasis (Bridi et al., ).…”
Section: The Synaptic Homeostasis Hypothesis Of Sleepmentioning
confidence: 99%
“…Nevertheless, the analysis of fluorescence intensity in the different immunoreactive puncta made our results more complex to interpret. The fluorescence intensity of VGLUT1 immunoreactive puncta decreased, suggesting a reduction in the expression of this molecule and thus in the transport of glutamate to synaptic vesicles, which may be related to the reduction of cortical activity after visual deprivation (Huang, Hokenson, Bandyopadhyay, Russek, & Kirkwood, ). It is interesting to note that VGLUT1 is only present in the synapses of excitatory cortical neurons and not in those of thalamo‐cortical axons, which express VGLUT2.…”
Section: Discussionmentioning
confidence: 99%